Benthic algal community dynamics on Palmyra Atoll throughout a decade with two thermal anomalies - Khen, Adi; Johnson, Maggie D.; Fox, Michael D.; Smith, Jennifer E. (Frontiers in Marine Science, 2025)
Coral reef algae serve many important ecological functions, from primary production to nutrient uptake and reef stabilization, but our knowledge of longer-term effects of thermal stress on algae in situ is limited. While ocean warming can facilitate proliferation of algae and potential phase shifts from coral to macroalgal-dominated states, algal responses may vary by species, genus, functional group, or type (e.g., calcareous vs. fleshy). We used 11 years of annual monitoring data (2009-2019) that spans two El Niño-associated heatwaves to examine benthic algal community dynamics on Palmyra Atoll in the central Pacific Ocean. We quantified the percent cover of algal taxa via image analysis of permanent benthic photoquadrats from two habitats on Palmyra: the deeper, wave-exposed fore reef (10 m depth) and the shallower, wave-sheltered reef terrace (5 m depth). Each habitat was characterized by distinct algal communities: predominantly calcareous taxa on the fore reef and predominantly fleshy taxa on the reef terrace. Patterns in abundance fluctuated over time and/or in response to thermal anomalies in 2009 and 2015. Fleshy algae generally increased in cover post-warming, which coincided with large declines of the calcified macroalgae, Halimeda spp. Long-term monitoring of coral reef algal communities is critical for understanding their differential responses to thermal stress and can improve projections of ecosystem functioning in the context of global change.